Nanoparticle-Based Modulation and Monitoring of Antigen-Presenting Cells in Organ Transplantation - Ochando, Jordi; Braza, Mounia S. (Frontiers in Immunology, 2017)
Donor-specific unresponsiveness while preserving an intact immune function remains difficult to achieve in organ transplantation. Induction of tolerance requires a fine modulation of the interconnected innate and adaptive immune systems. Antigen-presenting cells (APCs) predominate during allograft rejection and create a highly inflammatory context where allospecific T cells are primed. Currently, the available protocols to prevent allograft rejection include a cocktail of drugs that are efficient in the short-term, but with severe long-term side effects and considerable toxicity. Consequently, better and less burdensome strategies are needed to promote indefinite allograft survival. Targeted delivery of immunosuppressive drugs that prevent the alloimmune response may address some of these problems. Nanoparticle-based approaches represent a promising strategy to negatively modulate the alloresponse by specifically delivering small compounds to APCs in vivo. Nanoparticles are also used as integrating imaging moieties to monitor inflammation for diagnostic purposes. Therefore, nanotechnology approaches represent an attractive strategy to deliver and monitor the efficacy of immunosuppressive therapy in organ transplantation with the potential to improve the clinical treatment of transplant patients.